Effects of breed and protein supplementation on development of resistance to gastrointestinal parasites in sheep - Haile, Aynalem (Alemaya University of Agriculture, 1999)
The effects of breed and dietary protein supplementation on the development of resistance to endoparasites was examined in artificially infected lambs. The experimental design involved 2 breeds (Menz and Horro), 2 infection treatments (Infected vs Non-infected) and 3 dietary protein treatments using 152 lambs assigned to the 12 treatment combinations, with an average of about 13 animals per cell. Diets were formulated to be isocaloric but with varying protein and/or nitrogen sources. The nutritional control group of lambs were maintained on a basal diet of hay offered ad libitum, whereas, the second and third nutrition treatments consisted, in addition to the basal diet, of supplements of molasses-urea blocks (MUB) and cotton seed cake (CSC), respectively. Infection treatment involved repeated infection and drenching on three phases separated by periods of two weeks (between primary and secondary) and six weeks (between secondary and tertiary) during which lambs were free of worms. In the first two infections, the 'infected' group of lambs were exposed to an experimental infection of 1000 L3 (third stage larvae) of Haemonchus contortus given orally three times a week for 3 weeks. On tertiary infection however, mixed infections of Haemonchus contortus, Longystrongylus elongata and Trichostrongylus colubriformis involving a dose rate of 500 L3 given three times a week for 12 weeks.